Comparative Analysis of Cage Subsidence in Anterior Cervical Decompression and Fusion: Zero Profile Anchored Spacer (ROI-C) vs. Conventional Cage and Plate Construct - Jin, Zhe-yu; Teng, Yun; Wang, Hua-zheng; Yang, Hui-lin; Lu, Ying-jie; Gan, Min-feng (Frontiers in Surgery, 2021)
Background: Anterior cervical discectomy and fusion (ACDF) has been widely performed to treat cervical generative diseases. Cage subsidence is a complication after ACDF. Although it is known that segmental kyphosis, acceleration of adjacent segmental disease, and restenosis may occur due to cages subsidence; however detailed research comparing zero-profile cages (ROI-C) and conventional plate and cage construct (CPC) on cage subsidence has been lacking. Objective: The objectives of this study was to compare the rate of postoperative cage subsidence between zero profile anchored spacer (ROI-C) and conventional cage and plate construct (CPC) and investigate the risk factors associated with cage subsidence following ACDF. Methods: Seventy-four patients with ACDF who received either ROI-C or CPC treatment from October 2013 to August 2018 were included in this retrospective cohort study. Clinical and radiological outcomes and the incidence of cage subsidence at final follow up-were compared between groups. All patients were further categorized into the cage subsidence (CS) and non-cage subsidence (NCS) groups for subgroup analysis. Results: The overall subsidence rate was higher in the ROI-C group than in the CPC group (66.67 vs. 38.46%, P = 0.006). The incidence of cage subsidence was significantly different between groups for multiple-segment surgeries (75 vs. 34.6%, P = 0.003), but not for single-segment surgeries (54.55 vs. 42.30%, P = 0.563). Male sex, operation in multiple segments, using an ROI-C, and over-distraction increased the risk of subsidence. Clinical outcomes and fusion rates were not affected by cage subsidence. Conclusion: ROI-C use resulted in a higher subsidence rate than CPC use in multi-segment ACDF procedures. The male sex, the use of ROI-C, operation in multiple segments, and over-distraction were the most significant factors associated with an increase in the risk of cage subsidence.